Examining the relationship between taekwondo coaches’ attitudes towards coaching and their self-esteem - Sadik, Reşat; Pepe, Şirin (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study aimed to examine the relationship between taekwondo coaches’ attitudes toward the coaching profession and their self-esteem. The sample consisted of a total of 106 coaches, including 31 females (29.2%) and 75 males (70.8%). In addition to a demographic information questionnaire developed by the researchers, the “Attitude Scale Toward the Coaching Profession”, and the “Rosenberg Self-Esteem Scale” and adapted into Turkish were used. The research was conducted using a relational survey model. Since the data did not show a normal distribution according to the statistical analyses, non-parametric statistical methods were employed. Research findings revealed that there is a positive and moderately significant relationship between self-esteem and attitudes towards the coaching profession (p<0.05). This shows that coaches with high self-esteem develop more positive attitudes towards their profession, and this situation is related to multidimensional psychosocial variables such as professional motivation, communication skills, leadership qualities, and general life satisfaction. The fact that female coaches exhibit more positive results, particularly in the behavioral attitude dimension, also raises the need for more in-depth analysis of gender roles. Such findings highlight the fact that the coaching profession should be based not only on technical knowledge but also on psychological and social dimensions.